Simulations for a Model of a Competitive Economy Including Stock Levels - Naskręcka, Monika (Studia Oeconomica Posnaniensia, 2013)
Models of general equilibrium make it possible to determine equilibrium prices in a competitive economy. These models are not able to properly describe all the processes taking place in an economy. They do not take into consideration the necessity of storage that arises when there is an excess of products. Thus, the question arises about the influence of stock levels on market equilibrium (or disequilibrium) and stability. This paper will present a simple model of a competitive economy including stock levels and a simulation of the trajectories of prices and stock levels.